Alkyltriphenylphosphonium turns naphthoquinoneimidazoles into potent membrane depolarizers against mycobacteria. Issue 12 (26th October 2022) - Fridianto, Kevin Timothy; Gunawan, Gregory Adrian; Hards, Kiel; Sarathy, Jickky Palmae; Cook, Gregory M.; Dick, Thomas; Go, Mei-Lin; Lam, Yulin
Abstract : Herein, we establish the antimycobacterial activity of trialkylphosphonium-containing naphthoquinoneimidazoles, which exhibited limited redox activity but extensive membrane depolarization that resulted in depletion of ATP. Abstract : Due to its central role in energy generation and bacterial viability, mycobacterial bioenergetics is an attractive therapeutic target for anti-tuberculosis drug discovery. Building upon our work on antimycobacterial dioxonaphthoimidazoliums that were activated by a proximal positive charge and generated reactive oxygen species upon reduction by Type II NADH dehydrogenase, we herein studied the effect of a distal positive charge on the antimycobacterial activity of naphthoquinoneimidazoles by incorporating a trialkylphosphonium cation. The potency-enhancing properties of the linker length were affirmed by structure–activity relationship studies. The most active compound against M. tb H37Rv displayed good selectivity index (SI = 34) and strong bactericidal activity in the low micromolar range, which occurred through rapid bacterial membrane depolarization that resulted in depletion of intracellular ATP. Through this work, we demonstrated a switch of the scaffold's mode-of-action via relocation of positive charge while retaining its excellent antibacterial activity and selectivity.